Increasing transparency in assessment to improve studentsâ learning at Language Development Centre of UIN Suska Riau - Settiawana, Dodi; Hilmawan, Ridho (Sebelas Maret University, 2016)
In the foreign/second language classroom, assessment tasks are not just created to measure and document studentsâ performance at a given point in time. Effective assessment should be done through activities and tasks that teachers use to gather evidence and provide feedback about how well the students are performing. Therefore, the results of assessment can inspire the students to improve their learning. This paper is a work-in-progress report that describes several phases in the assessment process that were implemented at Language Development Center of UIN Suska Riau. This paper explores the key concepts for planning an assessment that is useful, valid, reliable, practical, and authentic. The application of transparency in assessment is also presented to provide practical guidance in sharing information about assessments before they occur using the Language Development Centerâs website. Ultimately, it is hoped that increasing transparency provides students of Language Development Center with chance to perform better or improve their learning because they receive a clear explanation of how the skills, vocabulary, and grammar that they are going to learn will be assessed.